PERENCANAAN PEMBELAJARAN KURIKULUM 2013 - ., nazar (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
In the development of education in Indonesia, a teacher must understand the development of the applicable curriculum, especially regarding competencies that have been set in content standards according to the enactment of the 2013 curriculum, from three aspects of competency in development to four competencies that must be mastered by a student after completing education in the unit education. The application process is carried out through the stages of planning and compiling competencies by describing the basic competencies until the formulation of indicators that can be measured, after going through a complete learning process and developing systematic learning material.